The Role of AI in Enhancing Workplace Wellness in the Healthcare Sector - Namita Priya1, Dr. Ipseeta Satpathy1, Dr. B.C.M. Patnaik1 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Employee Well-being has strategic relevance to the organizations and its employees and has been the focus of research and study as Workplace Wellness programs to ensure employee well-being, have primarily proved to improve productivity, reduce absenteeism, and foster a healthier and thriving workforce. Well-being has two dimensions hedonic and eudaimonic; Hedonic well-being is the pleasure and happiness that we derive from doing what we like i.e having positive emotional experiences like pleasure, enjoyment, eating good meals, spending time with friends, enjoying the work and work environment and avoiding what we dislike. Eudaimonic well-being refers to the experience associated with living a life of virtue and a broader definition of flourishing, that is derived from the higher order of Maslow’s needs like self-actualization, personal expressiveness, and vitality. Well-being thus encompasses both economic and financially driven matrices like health, income, community, culture, and work, and internal subjective experiences like psychological well-being, orientation towards human rights, environmental sustainability, and other related approaches thathavewide acceptance and legal standing. Employee well-being is a valuable tool and the highest priority of employers as employee well-being and employee engagement are strongly connected and it establishes a meaningful connection with employees regardless of where the employee works - from home, from the office, on a cruise, or in a manufacturing unit. Investment in well-being is the smartest investment by employers as the cost of neglecting well-being at work has a very high stake both for employees and employers